Phenotypic and genotypic characterization of carbapenem-resistant Gram-negative organisms, Beni-Suef, Egypt - Doaa Ghaith; Sara A. Morsy; Mohamed Sebak; Radwa A. Rabea (Beni-Suef University Journal of Basic and Applied Sciences, 2023)
Abstract Background Carbapenem-resistant Gram-negative organisms (CRGNO) are a growing threat. We aimed in our study to determine the genotype of carbapenemases at Beni-Suef University Hospital by using newly introduced lateral flow assays in comparison with molecular techniques and test the effectiveness of ceftazidime/avibactam against them. Methods Screening for carbapenemase production was done by mSuperCARBA (CHROMagar™ company). Genotypic characterization was done using 3 different kits of lateral flow assays: the NG-Test CARBA5 assay (NG Biotech, Guipry, France), RESIST-3 O.K.N. (Coris BioConcept, Belgium) and Carbapenem-resistant K.N.I.V.O Detection K-Set (Beijing Gold Mountain river Tech Development Co, China), whereas genotypic characterization was done for blaVIM blaIMP, blaKPC, blaOXA-48, and blaNDM by PCR. Results The high prevalence of CRGNO in Beni-Suef University Hospital (29%) was dominated by Klebsiella pneumonia (83.3%) harboring OXA-48 (92%). Lateral flow immunoassays showed high sensitivity and specificity for each type of carbapenemases in comparison with PCR. Conclusion The coexistence of multiple carbapenemases genes in the same isolate increased resistance to new therapeutic options, e.g., CZA/AVI. Proper implementation of isolation measures in health care facilities can render the spread of CRGNO.